Status and the Brain - Utevsky, Amanda V.; Platt, Michael L. (PLOS Biology, 2014)
Status and the Brain A neuroimaging study reveals regions in the monkey brain that track social status—Amanda V. Utevsky and Michael L. Platt put the new findings into context. See accompanying Research Article by MaryAnn P. Noonan, Matthew F. Rushworth, and colleagues.